The GHG balance of biofuels taking into account land use change - Mareike Lange (Kiel Institute for the World Economy (IfW), 2010)
The contribution of biofuels to the saving of greenhouse gas (GHG) emissions has recently been questioned because of emissions resulting from land use change (LUC) for the bioenergy feedstock production. We investigate how an expanding biofuel feedstock production impacts on land use dynamics if LUC is included into the biofuel carbon accounting framework as scheduled by the European Commission. We first illustrate the change in carbon balances of different biofuels, using methodology and data from the IPCC Guidelines for National Greenhouse Gas Inventories. It turns out that the conversion of natural land except for grassy savannahs impedes meeting the EU's 35% minimum emissions reduction target for biofuels. We show that the current accounting method promotes biofuel feedstock production mainly on former cropland, thus increases the competition between food and fuel production on the currently available cropland area. We further discuss whether it is profitable to use degraded land for commercial bioenergy production as requested by the European Commission to avoid undesirable LUC and conclude that the current regulation sets little incentives to use such land. The exclusive consideration of LUC for bioenergy production minimizes direct LUC at the expense of increasing indirect LUC but a convincing approach to implement indirect LUC into the framework does not exist. To overcome this problem, we propose the inclusion of all agricultural activities into a regulatory framework for carbon accounting, thus eliminating the indirect LUC risk.
Keywords: Q58; Q42; Q24; Q17; 330; Land use change emissions; bioenergy; biofuels; European policy; land use dynamics; indirect land use change (ILUC)